Encapsulation of metallic iron magnetic nanoparticles by polyacrylamide in water suspensions - A. Shankar; A. P. Safronov; I. Beketov (Chimica Techno Acta)
Theoretical consideration of the factors of the stability of metallic iron magnetic nanoparticles (MNPs) in water suspensions was done using extended DLVO (Derjaguin-Landau-Verwey-Overbeek) approach based on the balance among Van der Waals, electrostatic, magnetic and steric interactions.  Magnetic and steric interactions dominate over other in suspensions of Fe MNPs. To test the theory Fe MNPs with average diameter 84 nm were synthesized by electrical explosion of wire and encapsulated by polyacrylamide in water suspension to provide steric repulsion. It was shown that encapsulation resulted in the efficient diminishing of the aggregation of metallic iron MNPs in water.